Stratification of brachytherapy-treated intermediate-risk prostate cancer patients into favorable and unfavorable cohorts - Merrick, Gregory S.; Butler, Wayne M.; Galbreath, Robert W.; Fiano, Ryan; Adamovich, Edward (Journal of Contemporary Brachytherapy, 2015)
Purpose: To evaluate biochemical failure (BF) and prostate cancer specific mortality (PCSM) in intermediate-risk (IR) brachytherapy patients stratified into favorable and unfavorable cohorts, and to compare those outcomes to patients with low (LR) and high-risk (HR) disease. Material and methods : From March 1995 till February 2012, 2,502 consecutive patients underwent permanent interstitial brachytherapy for clinically localized prostate cancer. Patients were stratified into risk groups as per the NCCN guidelines with further stratification of the intermediate risk cohort into unfavorable (primary Gleason pattern 4, ≥ 50% positive biopsies or ≥ 2 IR features) and favorable cohorts. Median follow-up was 8.5 years. The brachytherapy prescription dose was prescribed to the prostate gland with generous periprostatic margins. Biochemical failure was defined as a PSA > 0.40 ng/ml after nadir. Patients with metastatic prostate cancer or non-metastatic castrate resistant disease who died of any cause were classified as dead of prostate cancer. Multiple parameters were evaluated for effect on outcomes. Results : Fifteen year BF for LR, favorable IR, unfavorable IR, and HR were 1.4%, 2.2%, 7.1%, and 11.1% (p < 0.001), respectively. At 15 years, PCSM for LR, favorable IR, unfavorable IR, and HR was 0.3%, 0.6%, 2.2% and 4.6% (p < 0.001), respectively. In multivariate analysis, BF was best predicted by risk group, pre-implant PSA, percent positive biopsies, prostate volume, and ADT duration, while PCSM was most closely related to risk group, percent positive biopsies and prostate volume. Conclusions : Patients with favorable IR disease have biochemical and PCSM outcomes comparable to those of patients with LR disease. Although unfavorable IR has greater than a 3-fold increased risk of BF and PCSM when compared to favorable IR, the outcomes remain superior to those men with HR disease.